MOODLE ENVIRONMENT AND ITS USE WITHIN FORMAL AND INFORMAL EDUCATION AT A VOCATIONAL SCHOOL - Garkule, Valentina; Makarevičs, Valērijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The widespread development of digital technology contributes to the creation of pedagogical innovations using e-learning and m-learning technologies. The platform (e-learning environment) MOODLE, which unites these technologies, makes it possible to master the educational material both within the field of formal, as well as within informal and non-formal education. The MOODLE environment has not been yet sufficiently used in general and vocational education. The possibilities of using this learning environment at vocational schools in Latvia and Poland are considered in the article. Students who studied programs using the capabilities of the MOODLE environment, after completing the training, have evaluated the importance of such work for the acquisition of professional knowledge and skills. To do this, they were asked to answer questions of the questionnaire. The content of the questions can be found in the text of the article. The study identifies general and regional features of learning outcomes using the MOODLE environment.